Tissular chromatin-state cartography based on double-barcoded DNA arrays that capture unloaded PA-Tn5 transposase - Mendoza-Ferri, Maria Grazia; Lozachmeur, Gwendoline; Duvina, Maximilien; Perret, Laetitia; Merciris, Didier; Gigout, Anne; Mendoza-Parra, Marco Antonio (Genome Research, 2025)
Recent developments in spatial omics are revolutionizing our understanding of tissue structure organization and their deregulation in disease. Here, we present a strategy for capturing chromatin histone modification signatures across tissue sections by taking advantage of a double-barcoded DNA arrays design compatible with in situ Protein A–transposase Tn5 tagmentation. This approach has been validated in presence of fresh-frozen mouse brain tissues but also in decalcified formalin-fixed paraffin-embedded (FFPE) mouse paw samples, in which either the histone modification H3K4 trimethylation or H3K27 acetylation has been used as proxy for interrogating active promoter signatures. Furthermore, because combinatorial enrichment of multiple histone modifications was shown to code for various states of gene transcriptional status (active, bivalent, repressed), we have integrated several histone modifications generated from consecutive mouse embryo sections to reveal changes in chromatin states across the tissue. Overall, this spatial epigenomic technology combined with the use of a spatial chromatin-state analytical strategy paves the way for future epigenetics studies for addressing tissue architecture complexity.
10.1101/gr.280305.124